Infiltrasi Paham Wahhabi Dalam Tafsir Al-Manar: Studi Kritis Terhadap Tafsir Ayat Sifat dalam Tafsir al-Manar Karya Rashid Rida - Masduki, Asyhari (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2020)
Tafseer Al-Manar is a controversial interpretation of the Qur'an. Some circles such as Aaron Nasution refer to the influence of Mu'tazilah in this interpretation, but on the other hand, there is also the smell of Wahhabi in it. The controversy of Al Manar's interpretation cannot be separated from the two authors, namely Muhammad Abduh and Rashid Rida. Muhammad Abduh was judged to be more liberal than his disciple, Rashid Rida. In order to prove Aaron Nasution's alleged, it was sufficient to study the views of Muhammad Abduh and Rashid Rida about the interpretation of the verses of the nature of Allah that they poured out in the interpretation of Al Manar. This paper proves that the interpretation of Al Manar is true in the interpretation of the verses of the nature of God following the interpretation of the group Wahhabi. The proof of Rashid Rida often quoted and defended the opinion of Ibn Taymiyah and Ibn al-Qoyyim al Jawziyyah (role model of the group Wahhabi).